1991
DOI: 10.2307/2409691
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Gene Flow in a Moving Hybrid Zone of the Newts Triturus cristatus and T. marmoratus in Western France

Abstract: Two hybridizing species of newts, Triturus cristatus and T. marmoratus, with overlapping distributions show a parapatric distribution when surveyed in detail. The factors that govern the distribution of cristatus vs. marmoratus in the département (province) of Mayenne in western France are identified as forestation and relief. The parapatric hybrid zone running through Mayenne is narrow but widens to approximately 20 km in an area with mixed habitat. In this area most breeding sites are shared and F hybrids fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
164
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(172 citation statements)
references
References 0 publications
8
164
0
Order By: Relevance
“…In addition to this spatial component, another limit to our conclusions comes from the lack of information on temporal variation. In such a Table 4 Estimates of Wrights F-statistics according to Weir & Cockerham's (1984) historical context, a hybrid zone should also be analysed over the dimension of time (Arntzen & Wallis, 1991 the Maghreb territory, they have probably been locally eliminated under the effects of genetic drift, mutation and/or selection as a result of their having low frequencies in the ancestral population (Slatkin, 1985). It is, however, surprising to observe so many private alleles among adjoining populations, an average of 19 alleles instead of the 13 ( = 4.1, P = 0.04) found in the remaining Maghreb colonies Guiller, Bellido & Madec, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this spatial component, another limit to our conclusions comes from the lack of information on temporal variation. In such a Table 4 Estimates of Wrights F-statistics according to Weir & Cockerham's (1984) historical context, a hybrid zone should also be analysed over the dimension of time (Arntzen & Wallis, 1991 the Maghreb territory, they have probably been locally eliminated under the effects of genetic drift, mutation and/or selection as a result of their having low frequencies in the ancestral population (Slatkin, 1985). It is, however, surprising to observe so many private alleles among adjoining populations, an average of 19 alleles instead of the 13 ( = 4.1, P = 0.04) found in the remaining Maghreb colonies Guiller, Bellido & Madec, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…A hybrid zone between lizards Sceloporus tristichus and Sceloporus cowlesi has moved over 1.5 km in around 30 years in favour of the former; correspondingly, S. cowlesi mitochondrial DNA is found introgressed over 8 km into the current range of S. tristichus (Leaché and Cole, 2007). Introgression between newts Triturus cristatus and Triturus marmoratus is found in the area of recent species replacement, but is absent in other areas (Arntzen and Wallis, 1991). At a hybrid zone between two warbler species, predominantly Vermivora chrysoptera mtDNA haplotypes are found in hybrids at the leading edge of a Vermivora pinus expansion (Dabrowski et al, 2005) and cytonuclear disequilibrium is also found at a crayfish Orconectes rustica-Orconectes propinquus hybrid zone.…”
Section: Relictual Populationsmentioning
confidence: 99%
“…The congruence between genetic data and classical morphological interpretations was then examined. Considering that the mitochondrial genome of a taxon can introgress into another closely related taxon (Arntzen and Wallis, 1991;Ruedi et al, 1997;Tegelstrom, 1987), a fragment of the nuclear gene Breast Cancer Susceptibility 1 (BRCA1) was analysed in certain samples. Using such data from both mitochondrial and nuclear genomes, and considering the molecular clock, the colonisation and diVerentiation of the populations through time and space was reconstructed.…”
Section: Article In Pressmentioning
confidence: 99%